2011
DOI: 10.1007/s11738-011-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of pigment in fiber related to proanthocyanidins synthesis for brown cotton

Abstract: Brown cotton is a kind of naturally colored cotton. Because of less processing and little dying, it is more friendlier to environment than white cotton. For brown cotton, pigment accumulation in fiber is one of the most important characteristics. In this study, we selected a brown fiber line and a white fiber cultivar to determine the factor that affects the pigmentation in brown fiber. Accordingly, fibers were collected to verify the presence of PAs by p-dimethylaminocinnamaldehyde (DMACA) and toluidine blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 14 publications
(25 reference statements)
7
28
0
Order By: Relevance
“…Previous studies demonstrated that the transcription of flavonoid genes and PA was more abundant in brown fiber than in white fiber Li et al, 2011). Our further analysis indicated that the other flavonoids were also abundant in brown fiber (Supplemental Table S3).…”
Section: F3h Is More Important To Brown Fiber Development Than It Is supporting
confidence: 52%
“…Previous studies demonstrated that the transcription of flavonoid genes and PA was more abundant in brown fiber than in white fiber Li et al, 2011). Our further analysis indicated that the other flavonoids were also abundant in brown fiber (Supplemental Table S3).…”
Section: F3h Is More Important To Brown Fiber Development Than It Is supporting
confidence: 52%
“…Manuscript to be reviewed of PAs in the fibers of brown cotton at different developmental stages ( Figure 6). The determination of PAs showed that both soluble and insoluble PAs had mainly accumulated before DAF, after which its content gradually decreased; these results were consistent with the previously reported results (Li et al, 2012). Interestingly, GhPKS4, 5, 9, 11 had a higher level of transcription at the early stages of cotton fiber development; the amount of expression then decreased gradually, which is consistent with the rule of accumulation of PAs in brown cotton fibers.…”
Section: Expression Characteristics Of the Pks Gene In Upland Cottonsupporting
confidence: 91%
“…Tannins are complex, poly-phenol, and amorphous compounds that are present in plants. Histochemical staining and colorimetric reactions of developing and mature cotton fibers showed that condensed tannins are responsible for the color of brown cotton fiber (Hua et al 2007;Li et al 2012;Xiao et al 2007). Consistently, the intensity of the characteristic peaks of condensed tannins was diminished for the SA-1 fiber with a lighter brown shade.…”
Section: Resultsmentioning
confidence: 99%